SUSTAINABLE FINANCING ACCOUNTING : ASSITALLASSI CONCEPT - Sultan Syah (Assets: Jurnal Akuntansi dan Pendidikan, 2021)
ABSTRACTThis research constructs the concept of assitallassi (mutual support) applied by the patorani community for sustainable financing accounting. The research method used is a qualitative method with an interpretive paradigm. For the data collection, the researchers used two approaches simultaneously, namely institutional and ethno-methodological. The researchers chose qualitative data and obtained data directly from the field (primary data) as research data. Accounting practice begins with recording the funding and profit-sharing of the catch during a season. The important conclusion of this research is that accounting is related to material and no material aspects. The accounting system for financing and profit-sharing in the community of Patorani is not absolute but tailored to needs. It all depends on the agreement of all parties during the assikko' kana (hybrid contract).ABSTRAKPenelitian ini mengkonstruksi konsep assitallassi (Saling menghidupi) yang diterapkan oleh komunitas patorani untuk akuntansi pembiayaan berkelanjutan. Metode penelitian yang digunakan adalah metode kualitatif dengan paradigma interpretif. Untuk perolehan data, peneliti menggunakan dua pendekatan sekaligus yaitu institusional dan etnometodologi. Peneliti memilih data kualitatif dan perolehan data secara langsung diambil dari lapangan (data primer) sebagai data penelitian. Praktek akuntansi dimulai dari mencatat pembiayaan dan bagi hasil atas hasil tangkapan selama satu musim. Temuan penting dalam penelitian ini yaitu akuntansi tidak hanya terkait dengan materi tetapi aspek non materi. sistem akuntansi pembiayaan dan bagi hasil pada komunitas patorani tidak bersifat mutlak tetapi disesuaikan dengan kebutuhan. Semua tergantung kesepakatan semua pihak ketika assikko’ kana (hybrid contract).